Case Report: Variations in the ALPL Gene in Chinese Patients With Hypophosphatasia - Zhang, Qiang; Qin, Zailong; Yi, Shang; Wei, Hao; Zhou, Xun zhao; Shen, Fei (Frontiers in Genetics, 2021)
Background: Hypophosphatasia (HPP) is an autosomal genetic disorder characterized biochemically by abnormal of bone parameters and serum alkaline phosphatase (ALP) activity as well as clinically by deficiency of teeth and bone mineralization. The clinical presentation is a continuum ranging from a prenatal lethal form with no skeletal mineralization to a mild form with late adult onset presenting with non-pathognomonic symptoms. ALP deficiency is the key to the pathogenesis of abnormal metabolism and skeletal system damage in HPP patients. Methods: We investigated 5 patients with skeletal dysplasia in the clinic. Whole-exome sequencing was performed in order to aid diagnosis of the patients. Results: Eight variants in the ALPL gene in the five unrelated Chinese patients (PA-1: c.649_650insC and c.707A>G; PA2: c.98C>T and c.707A>G; PA3: c.407G>A and c.650delTinsCTAA; PA4: c.1247G>T (homozygous); PA5: c.406C> T and c.1178A> G; NM_000478.5) were found. These variations caused two types of HPP: perinatal HPP and Odonto HPP. All cases reported in this study were autosomal recessive. Among the variants, c.1247G>T/p.Gly416Val (PA-4); c.1178A>G/p.Asn393Ser (PA-5) and c.707A>G/p.Tyr236Cys (PA-1, PA-2) have never been reported before. Conclusions: Clinical phenotypes of perinatal HPP（PA-1,PA-2,PA-3 and PA-4）include skeletal dysplasia, shorter long bones, bowing of long bones, tetraphocomelia, abnormal posturing and abnormal bone ossification. Odonto HPP (PA-5) only presents as dental abnormality with severe dental caries and decreased ALP activity. Our study extends the pool of ALPL variants in different populations.